Efeito de gradientes ambientais na estruturação da comunidade de morcegos insetívoros aéreos em uma floresta contínua na Amazônia central - Cabral, Ricardo Cesar Correa (Instituto Nacional de Pesquisas da Amazônia - INPA, 2023)
Environmental factors influence how species select habitat and are spatially distributed in the environment. Topography, vegetation structure and food availability have been identified as factors that directly and indirectly influence habitat selection by species in tropical forests. Bats are a promising model to study the relationship between environmental characteristics and species distribution, as the group has high diversity and abundance in tropical regions. Neotropical aerial insectivorous bats have been neglected and studies that evaluated how environmental factors explain species distribution and abundance were conducted in altered environments. Therefore, our knowledge of the factors that determine the structuring of the aerial insectivorous bat community is still low. In this study, we evaluated how aerial insectivorous bats respond to different environmental gradients in 25 km2 of continuous forest in Central Amazonia. Our hypothesis was that topography, vegetation structure and food availability influence aerial insectivorous bats. Insect mass was the predictor variable with the greatest contribution to the richness, abundance and composition of bat species. Bat activity and richness were positively related to insect mass. The species composition of bats was related to altitude and insect composition. Clutter vegetation was not enough to influence the number of species, abundance and species composition of bats. Altitude had a positive relationship with aerial insectivorous bat species composition. Insect mass and composition were the predictors for aerial insectivorous bat community structuring compared to vegetation uplift and obstruction in a continuous forest in Central Amazon.
Effect of environmental gradients on community structuring of aerial insectivorous bats in a continuous forest in Central Amazon
Keywords: Biologia e ecologia de morcegos insetívoros aéreos